Road traffic injury mortality, morbidity and disability: evidence from Bangladesh Health and Injury Survey (BHIS). (7th October 2012) - Baset, MK; Rahman, A; Mashreky, SR; Talab, A; Rahman, A K M F; Towner, E
Abstract : Introduction: Road traffic injuries (RTIs) are a leading cause of morbidity, disability and mortality in low income countries. In 2004 nearly 1.3 million people of all ages were killed in road traffic crashes and over 50 million were injured or disabled. There are indications that road traffic injury fatalities and morbidities are increasing in Bangladesh. Objective: Investigate the magnitude of and risk factors for road traffic injury in Bangladesh. Methodology: A cross sectional study was conducted to explore the magnitude of mortalities and disabilities due to RTIs. Face-to-face interviews were used. Multi stage cluster sampling was used to select the sample. Results: Data were collected from 171 366 rural and urban households, covering a population of 819 429. The overall incidence of RTIs fatality was 12.9 per 100 000 population. The mortality rate gradually rose from children under five and peaked in the older age group, 55 years and above, (21.4 per 100 000). The overall rate of non-fatal RTI was calculated as 134.5 per 100 000. The highest incidence (165.7 per 100 000) was in the 20–39 years age group. A significantly higher rate of RTI mortality and morbidity was observed among males. The incidence of RTI was found to be three times higher in rural than urban areas. Most RTIs were non motorised vehicle and pedestrian injuries. The highest rate of RTI disability was found among males, aged 30–54 years. Conclusions: Road traffic injury is an important public health issue in Bangladesh. Immediate attention should be made to strengthen preventive intervention measures.